Moderate walnut consumption improved lipid profile, steroid hormones and inflammation in trained elderly men: a pilot study with a randomized controlled trial - Kamoun, Anis; Hammouda, Omar; Turki, Mouna; Maaloul, Rami; Chtourou, Mohamed; Bouaziz, Mohamed; Driss, Tarak; Souissi, Nizar; Chamari, Karim; Ayadi, Fatma (Biology of Sport, 2021)
The present study aimed to investigate the effect of walnut consumption on lipid profile, steroid hormones and inflammation in trained elderly men performing concurrent (resistance and endurance) training. Twenty healthy elderly males were divided into two matched groups, in a randomized controlled trial, that trained three sessions per week: concurrent training + dietary walnut consumption (15 g/day for six weeks, CTW: n = 10); concurrent training + control diet (CT: n = 10). Fasting blood samples were taken 48 hours before and after intervention for biochemical assessments. levels of high-density lipoprotein (HDL) increased only in CTW compared to baseline (19.8%, p < 0.01). Total cholesterol (TC), low-density lipoprotein (LDL) and triglyceride (TG) levels significantly decreased only for CTW (i.e., 13%, 18%, and 18.5% at p < 0.01 for all). Testosterone (T) increased after the training compared to pre-training for CTW and CT (10.3%, p < 0.01, 4.27% p < 0.05, respectively), but the increase was significantly higher in CTW (p < 0.05). Serum cortisol (C) was lower for CTW compared to CT (p < 0.01). C-reactive protein (CRP) decreased in CTW in comparison with CT. The present study revealed that 6-week moderate walnut supplementation (15 g/day) improved lipid profile, steroid hormones and systematic inflammation in aged men performing concurrent training. These findings could be attributable to the potential effect of polyunsaturated fatty acids (PUFA) contained in walnut (linoleic acid, n-6; linolenic acid, n-3).